A expansão das milícias no Pará: os vínculos transnacionais e a simbiose com o crime organizado - Lopes, Ian Nunes Dias (2024)
Militias in Brazil have unique characteristics and their own specific definition. They are a security problem that influences politics, culture, and the economy, directly affecting the outskirts of metropolises susceptible to conditions favorable to organized crime. Studying the roots of militia crime formation in Rio de Janeiro allows for a case study focused on analyzing the emergence of militias in cities like Belém, in the state of Pará. This analysis involves understanding the nuances of the militia phenomenon in Brazil, its comparison with Italian mafias, and its migration processes, with a focus on migration to new territories in three favorable scenarios: the growth of criminal factions in Pará, interactions with the illegal lottery (jogo do bicho), and expansion through police exchanges. The main objective of the dissertation is to examine the process of expansion of the militia model from Rio de Janeiro to Pará, delving into the factors that led to a rapid synergy between Pará's militias and criminal factions. The study aims to analyze how militia models across their various segments establish themselves in new locations. The methodology includes a literature review, document analysis, and interviews. Semi-structured interviews were conducted with sources directly connected to Pará's police force and individuals with direct or indirect experiences with militias. Contacts were obtained through a snowball sampling method, allowing for a range of plural sources. Data analysis criteria were applied in triangulation to the content gathered from the interviews. The findings reveal that the expansion of militias in Pará exemplifies one of the most entrenched militia phenomena in Brazil, stemming from a series of state decisions and omissions, contrastedby a concrete and effective encouragement of organized crime by its supporters.